Pengaruh Competition Intensity terhadap Bankruptcy Risk melalui Earning Management Sebagai Variabel Intervening pada Perusahaan Manufkatur di Surabaya dan Sidoarjo - Irine Virginia Soetanto; Devie Devie (Business Accounting Review, 2016)
This thesis aimed to know the significant direct affect of competition intensity to earnings management, earnings management to bankruptcy risk, and competition intensity to bankruptcy risk in manufacturing companies in Surabaya and Sidoarjo. This study also used to know a significant indirect affect of competition intensity on bangkruptcy risk through earnings management as intervening variables. The result indicated a positive and significant relationship of competition intensity to earnings management, earnings management to bankruptcy risk, and competition intensity to bankruptcy risk. Yet earnings management was inadequate to become as variable intermediary between competition intensity with bankruptcy risk because of the direct relationship between competition intensity with bankruptcy risk gave greater influence than through earnings management.